2004
DOI: 10.1002/hed.20046
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of HPV16‐associated head and neck squamous cell carcinoma in the Puerto Rican population

Abstract: Our findings suggest that HPV16 may play a role in the etiology of a subgroup of HNSCC in Puerto Ricans. Overall survival times of the HPV16-positive patients were not significantly different from those of HPV16-negative patients. Increasing our understanding of the role of HPV16 in the etiology of HNSCC might facilitate the development of new treatment modalities for this subgroup of HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
0
32
0
4
Order By: Relevance
“…82 The presence of HPV DNA in a significant fraction of OSCC raised the question of whether HPV tumor status affects the outcome of oral cancer. To date, the findings have been inconsistent, with some studies reporting no survival differences 84,87,94 and others clearly stating a reduction in death risk among patients with HPVpositive tumors when compared with those with HPVnegative tumors. 82,83,88,[90][91][92] A large study conducted by Gillison et al 82 has shown that patients with HPVpositive tumors had a 60% reduction in risk of death from cancer and significantly improved disease-specific survival when compared patients with HPV-negative tumors.…”
Section: Review Of the Literature Patient-related Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…82 The presence of HPV DNA in a significant fraction of OSCC raised the question of whether HPV tumor status affects the outcome of oral cancer. To date, the findings have been inconsistent, with some studies reporting no survival differences 84,87,94 and others clearly stating a reduction in death risk among patients with HPVpositive tumors when compared with those with HPVnegative tumors. 82,83,88,[90][91][92] A large study conducted by Gillison et al 82 has shown that patients with HPVpositive tumors had a 60% reduction in risk of death from cancer and significantly improved disease-specific survival when compared patients with HPV-negative tumors.…”
Section: Review Of the Literature Patient-related Factorsmentioning
confidence: 99%
“…There is escalating evidence of a causal association between HPV and OSCC, [82][83][84][85][86][87][88][89][90][91][92][93] with several studies showing that HPV is associated with increased risk of oral cancer, independently of exposure to tobacco and alcohol. 84,86,88,89 This association is valid for high-risk HPV, which comprises subtypes 16, 18, 33, and 35. HPV-16 may be responsible for more than 80% of HPV-positive OSCC.…”
Section: Review Of the Literature Patient-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Separately, the HPV 16 detected in larynx was 85.7% and 55.6% in hypopharynx. When aggregated, the hypopharynx and larynx showed 56% (29 cases) of all HPV16 DNA detected in the study (Báez et al, 2004).…”
Section: Larynx Cancersmentioning
confidence: 76%